THE INFLUENCE OF PROMOTION AND SERVICE QUALITY ON THE PURCHASE DECISION OF BAKMI DUA SAUDARA - Iis Noviyanti; Lia Asmalah; Juwita Ramadani Fitria (International Journal Management and Economic, 2024)
This research aims to partially and simultaneously determine the influence of promotion and service quality on purchasing decisions. The object of this research is consumers of Bakmi Dua Saudara, located in Gunung Sindur District, Bogor Regency. The sample formulation was based on the Slovin formula, namely 71 respondents. This research method is Multiple Regression Analysis with SPSS version 26. The results of this research are that partial promotion has a significant effect on purchasing decisions. Service quality partially has a significant effect on purchasing decisions. Promotion and service quality significantly affect purchasing decisions; the coefficient of determination value is 37.6, with 37.6% of the variation in purchasing decisions being explained by promotion and service quality together, other factors influence the remainder.